Metadherin overexpression in perihilar cholangiocarcinoma is associated with lymph node metastasis and poor prognosis - Zhu, Yan-Zhi (Oncol Lett, 2019)
Metadherin (MTDH) is a protein that is also named astrocyte elevated gene-1, and is highly expressed in a number of different tumor tissues. Although the expression of MTDH is associated with tumor invasion and recurrence, the expression of this protein in perihilar cholangiocarcinoma (PCCA) and its clinical use have not yet been investigated. In the present study, the expression of MTDH in patients with PCCA was investigated in order to determine its clinicopathological use. An immunohistochemical method was used to detect MTDH expression and the epithelial-mesenchymal transition markers E-cadherin and vimentin in 66 cases of PCCA. In addition to the expression of MTDH, the clinical and pathological data and the postoperative outcomes were analyzed. The MTDH positive expression rate was 48.5% (32/66) in PCCA. A significantly higher MTDH expression level was identified in the poor tumor differentiation group compared with the well differentiation group (P=0.007). In the positive lymph node metastasis group, a significantly higher MTDH expression level was revealed compared with the negative lymph node metastasis group (P=0.023). No association was noted with regard to the expression of MTDH and the variables age, sex, tumor diameter, tumor grade and tumor classification stage. Positive MTDH expression was significantly associated with high vimentin expression (P=0.037) compared with negative vimentin expression and inversely associated with positive E-cadherin expression compared with negative E-cadherin expression (P=0.030). Survival analysis suggested that the high MTDH expression group was associated with a worse overall survival (OS) rate and recurrence free survival (RFS) rate compared with the low MTDH expression group (P<0.001 and P=0.01, respectively). Cox regression analysis indicated that the Tumor-Node-Metastasis, surgery margin and high MTDH expression were independent OS and RFS factors for PCCA. MTDH expression may serve an important function in PCCA tumor growth and metastasis. Targeting MTDH may have important therapeutic applications for patients with PCCA.